Estudo do processamento de polietileno de ultra-alta massa molar(Peuamm)e polietileno glico (PEG) por moagem de alta energia - Gabriel, Melina Correa (2010)
The intention of this exploratory research is to study the modifications provided by high-energy mechanical milling in ultra-high molecular weight polyethylene (UHMWPE) and mixtures of this polymer with polyethylene glycol (PEG). These modifications can be of interest for future processing of UHMWPE. The mechanical milling was performed in an attritor mill, a type of mill that can be used in laboratory as well as in industry. The millings of UHMWPE were performed in different rotation speeds. For mixtures of UHMWPE and PEG, the amounts of PEG were also different. The samples were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The mechanical milling modified the UHMWPE particles morphology: with milling, the almost rounded shape became flat-like shape. This caused the reduction of apparent density of polymer after milling. The mechanical milling also provided structural changes. With the increasing of the rotation speed,there was the increasing of the monoclinic phase and the decreasing of the orthorhombic, up to 500 rpm. For 600 rpm, the amount of monoclinic phase decreased. In this rotation, the deformation rate probably increased the process temperature, allowing the monoclinic phase to return to its initial structural orthorhombic form. In mixtures of UHMWPE and PEG, after mechanical milling, the particles of PEG were probably reduced and better dispersed in the UHMWPE matrix. Changes in thermal characteristics of polymers also could be noted. The kinetics of UHMWPE crystal growth changed, as well as the behavior of PEG crystallization. Feasibly, dispersed particles of PEG acted as physical barriers against the crystalline phase growth of UHMWPE and the crystallization temperature of PEG decreased, when the UHMWPE and PEG mixtures were milled.